Percepções, atitudes e expectativas de agentes comunitários de saúde sobre usuários de drogas e seu processo de cuidado - Batista, Karen (2016)
The Ministry of Health's policy for integral care to drug users calls for social integration and the promotion of autonomy of these subjects through place-based approaches and community with the participation of users and families in the care process, and social control assistance. The competent care model for this is the Family Health Strategy (FHS), which includes the Community Health Workers (CHW). These CHW are professionals who mediate between the community and the health team in the care process. To support the qualification of these professionals to care for people who use licit and illicit drugs, we investigated the perceptions of the same on these users through a qualitative research previously approved by the Ethics Committee on Human Research of the Federal University of São Carlos, SP. To identify the CHW with experience in the care of people who use drugs to the interviews, the quantified experience of each one through a window specifically for this, applied to the total of 43 of these professionals working in health teams family under the single Family Health Support Centers of Rio Claro, SP, at the time of the study. Interviewing the CHW in descending order of the scores given by the experience rating indicator of each was obtained saturation of findings at the end of the tenth semi-structured interview. In light of the theoretical framework of the clinic of the subject and the integral care, we analyzed the speeches of the interviewed by thematic categories. The findings suggested a predominance of moralizing perceptions about the use and on and drug users, understanding these people as devoid of reason, requiring police intervention, legal or repressive nature of health. Against the Psychiatric Reform and social rehabilitation, there was institutionalization of expectations and an outsourcing of care, although at times the CHW own question the effectiveness of practices based on hospital-centric psychiatry. Overall, it was found that there are still actions based on common sense and lack of access to technical and scientific information that are reflected in disparaging view of the user and discomfort in dealing with them. Initiatives of a comprehensive care, which considers and promotes the autonomy of the subject were found in a few moments; significant of them understood as impact of its participation in the Care Pathways course, offered by the Ministry of Health to improve care to drug users under the ESF. Such a course has shown as the only training that CHW received on care to drug users. It was concluded that still prevails a stigmatizing view by CHW about who uses drugs, from a still lay understanding of the matter. However, there is provision of these professionals qualify this view and address the problem of use and drug users in the community in which they operate. Therefore, the development of matrix support spaces and regular Continuing Education projects for CHW and other Family Health Strategy professionals is appropriate to have such discussions and qualify the care of drug users.